Pengembangan Kemojo Tinggi Protein Berbasis Bahan Lokal di Kelurahan Melebung untuk Meningkatkan Nilai Gizi Kue Tradisional - Yunelfia Yunelfia; Arnila Melina; Ami Amelia; Mahendra Mahendra; Rizka Prasetya; Fatimah Azzhra; Arzita Diandra; Hayatun Daskia Maranti (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2025)
This study focuses on developing the traditional Kemojo cake by enhancing its protein content using locally sourced ingredients available in Kelurahan Melebung. Traditionally known as a carbohydrate- and fat-rich delicacy, Kemojo has been innovated by incorporating protein-rich ingredients such as nuts, seed-based flours, and other local protein sources. The use of local materials aims not only to improve the cake's nutritional value but also to utilize natural resources, support food security, and boost the local economy by promoting healthier food products. This initiative seeks to introduce Kemojo as a more nutritious traditional food alternative suitable for all age groups, including children, adolescents, and the elderly, who require higher protein intake. The improved nutritional value can play a significant role in addressing daily nutritional needs and reducing malnutrition, particularly in vulnerable regions. Additionally, utilizing local ingredients contributes to strengthening the local economy by empowering farmers and supporting food processing industries based on regional resources.